Activating the digital tourism media in promoting the culture of foreign tourism in Algeria : Analytical and critical reading - Karima Abba (Social Empowerment Journal, 2023)
Tourism is classified today, as well as major modern industries, for its prominent role in the development of various sectors, economic, social and cultural, Therefore, tourism agencies resorted to using the media, which bears the responsibility of promoting the tourism product, and addressing the masses through its various new digital means and forms, of which the Internet is the most widely in the marketing and revitalization of the tourism sector, because is considered the most popular means and consumption by members of the communities, which is responsible for the transfer and provide the attractions of each tourist destination without the other, in the framework of highlighting the local culture of each country and maintaining it. Despite the availability of Algeria on the elements of tourism natural, historical, civilization, but thier tourist agencies still suffer from a lack of quality of information services, which has not yet risen to the level of aspirations of foreign tourists in particular, which revealed the weakness of  the composition of human resources specialized in the field of  digital tourism media, and the weakness of information and communication strategies adopted by these institutions, Which led to aversion among tourists on the one hand, and the stagnation of foreign tourism on the other hand, where does this research paper aim by adobting the critical analytical method to address the issue of activating digital tourism media, and its importance as a strategic solution to spread the culture of foreign tourism and development in algeria.